1998
DOI: 10.1038/sj.bmt.1701465
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of peripheral blood progenitor cells after induction chemotherapy (THP-doxorubicin-vinorelbine-cyclophosphamide-fluorouracil) and granulocyte colony-stimulating factor in breast cancer

Abstract: Summary:In order to evaluate the mobilization of peripheral blood progenitor cells (PBPC) after an effective induction regimen in breast cancer, we performed a study on 15 breast cancer patients. Between January 1995 and June 1996, these patients received TNCF (THP-doxorubicin, vinorelbine, cyclophosphamide, fluorouracil for four days, every 21 days) with G-CSF support (5 g/kg for 10 days after chemotherapy) to reduce aplasia. This regimen is known to result in a complete pathological response in 30% of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Studies in vitro have shown that GM-CSF acts earlier than G-CSF. 15,16 In a previous study, we have shown a specific cytotoxic effect on breast tumor 21 and at the same time, mobilization of PBPC 20 after TNCF treatment and G-CSF. In the present work, we looked for a synergistic effect of GM-CSF and G-CSF to improve hematological recovery between two TNCF cycles and to mobilize a sufficient number of PBPCs in one leukapheresis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in vitro have shown that GM-CSF acts earlier than G-CSF. 15,16 In a previous study, we have shown a specific cytotoxic effect on breast tumor 21 and at the same time, mobilization of PBPC 20 after TNCF treatment and G-CSF. In the present work, we looked for a synergistic effect of GM-CSF and G-CSF to improve hematological recovery between two TNCF cycles and to mobilize a sufficient number of PBPCs in one leukapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our results were two-to three-fold greater than those obtained with different mobilization regimens in breast cancer. 20,[27][28][29][30] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where E is the efficiency of CD34+ cell collection and C is CD34 level available to the apheresis instrument. Published data suggest that, during the initial phase of mobilization, A can be modeled by an exponential function 2,3 . The primary variables, then, which determine the number of CD34+ cells collected during a procedure are the number of BVs processed, the collection efficiency (at any given set of collection parameters), and the CD34 concentration available to the apheresis instrument, which depends upon a dynamic relationship between the mobilization and extraction of CD34+ cells.…”
mentioning
confidence: 99%
“…Breast cancer represents one of the most frequent disease entities treated with autologous PBPC transplantation, 1 although, in view of recent clinical results, the frequency of PBPC harvest in breast cancer patients may decrease in future 9 . Cyclophosphamide (CY) followed by the administration of G–CSF is a frequently applied protocol for PBPC mobilization in breast cancer 10,11 . Other regimens consisting of different cytoreductive agents have also been successfully used for PBPC mobilization 12,13 .…”
mentioning
confidence: 99%